Comparison between scarp and dip-slope rivers of the Cotswold Hills, UK. Issue 1 (February 2018) - Paul, Jonathan D.; Watson, Nick; Tuckwell, Edward
Abstract: The Cotswold Hills, southwest UK, are properly described as a cuesta, with a steep, west-facing scarp slope and a plateau-like dip slope. Drainage reflects this surface morphology, with most rivers flowing southeast along topographic and stratigraphic dip. Here, we compare two superficially highly similar rivers – the Frome and Churn – whose sources are nearly coincident, but whose behaviour dramatically diverges thereafter. We examine longitudinal profiles, channel steepness, predicted discharge, and valley shapes, using digital topographic data. River discharge and water hardness/temperature values were obtained at seven sites on the Churn and nine on the Frome over a two-year sampling campaign, delineated into summer and winter phases. Nearly 100 borehole records were interrogated from the two catchments in order to assess groundwater level variations. The Frome, flowing west against regional dips, develops a steep course and has carved a deep and wide valley that exposes the full sequence of Cotswold Jurassic stratigraphy. On the other hand, discharge and channel gradients are lower for the dip-slope Churn, whose valley exposes less stratigraphy and fewer springs. Our measurements of river water hardness and temperature suggest that a greater proportion of groundwater flows into the Frome, regulating discharge and maintaining baseflow over summer. We suggest that flank uplift of the Cotswolds is at least part of the reason for the higher incision rates of the River Frome, leading to its intersecting a greater number of highly transmissive fractures that contribute to its discharge. In turn, the increased discharge could positively impact local incision rates.